Prospective multicentre randomised, double-blind, equivalence study comparing clonidine and midazolam as intravenous sedative agents in critically ill children : the SLEEPS (Safety profiLe, Efficacy and Equivalence in Paediatric intensive care Sedation) study /: the SLEEPS (Safety profiLe, Efficacy and Equivalence in Paediatric intensive care Sedation) study. (December 2014) - Wolf, Andrew
No abstract available